The Supermakets Global Chain - Zomkowksi Salvi, Vinícius (Archives of Business Research, 2020)
Successful business depends on successful internal and external Supply Chain. From company requirements to tier supplier relationship, companies want to gain and keep customers. This article studied Supermarket supply chains. It tried to find positive and negative attributes, it did a gap analysis of those attributes and it dedicated deeply in techniques of integration and synchronization such as VMI, ECR and CPRF to prove the importance of a successful supply chain management. It was got 14 positive and negative attributes such as POS data, collaborative planning, collaborative and automatic replenishment, controlled inventory and developed logistics tools as cross docking, third parties, and RFID. Negative attributes can be, for instance, a complexed logistics operations and difficulties in implementing synchronization.